The impact of painful knee osteoarthritis on mortality: a community-based cohort study with over 24 years of follow-up. Issue 4 (April 2019) - Cleveland, R.J.; Alvarez, C.; Schwartz, T.A.; Losina, E.; Renner, J.B.; Jordan, J.M.; Callahan, L.F.
Summary: Objective: To investigate the impact of knee osteoarthritis (OA) and/or knee pain on excess mortality. Method: We analyzed data from 4, 182 participants in a community-based prospective cohort study of African American and Caucasian men and women aged ≥45 years. Participants completed knee radiographs and questionnaires at baseline and at up to three follow-ups to determine knee OA (rOA), knee pain and covariate status. Mortality was determined through 2015. We used Cox proportional hazards regression with time-varying covariates (TVC) to estimate hazard ratios (HR) and 95% confidence intervals (CI). Additional analyses stratified by sex, race and age were carried out. Results: Median follow-up time was 14.6 years during which 1822 deaths occurred. Baseline knee radiographic osteoarthritis (rOA) was 27.7%, 38.8% at first follow-up, 52.6% at second follow-up and 61.9% at the third follow-up. Knee rOA with pain and knee pain alone were both associated with a >15% increase in premature all-cause mortality. In analyses stratified by sex, race and age, associations between knee pain, with or without knee rOA, and all-cause death were found among women, Caucasians, those ≤65 years of age, and those with a body mass index (BMI)≥30, with observed increased risks of death between 21% and 65%. We observed similar, somewhat attenuated, results for cardiovascular disease (CVD) deaths. Conclusion: In models taking into account variables that change over time, individuals who had knee pain, alone or with knee rOA, had increased mortality. These effects were particularly strong among those obese. Effective interventions to reduce knee pain, particularly those including weight management and prevention of comorbidities, could reduce mortality.